EGGS AND EARLY DEVELOPMENTAL STAGES OF HILSA KELEE (CUVIER) - Rao, K Satyanarayana (Indian Journal of Fisheries, 2011)
A type of clupeiod fish eggs 1.005-1.065 mm in diameter with six or sevenoil globules recorded in the plankton off Madras coast from February to Apriland in December in 1967 and in January and March in 1968 have been ascribedto Hilsa kelee (Cuvier) based on the structure of the eggs and larvae hatchingfrom them, the simultaneous occurrence of ripe fish of the species in inshorewaters of Madras and coincidence of myotome number of larvae with the numberof vertebrae in adult fish.